Emerging Therapies in Penile Cancer - Alencar, Antonio Machado; Sonpavde, Guru (Frontiers in Oncology, 2022)
Advances in the treatment of rare tumors like penile cancer were always hampered by the lack of deep comprehension of the molecular biology and genomic and epigenomic alterations involved in carcinogenesis and tumor progression, as well as by the difficulty in recruitment of patients for prospective clinical trials. Despite the high rates of cure in early localized penile cancers with surgery or other local procedures, locally advanced and metastatic tumors require systemic treatment, with chemotherapy being the current standard, but with high toxicity and no proven real impact on survival. Recent important findings of frequent genomic alterations and mutation signatures in penile cancer have motivated several trials in new modalities of systemic treatments, especially immunotherapy. This review aims to present the most recent advances and the prospect of new modalities of systemic therapies with ongoing studies in penile cancer.